Decomposing Process of Food Waste using Black Soldier Fly Larvae (BSFL): Case Study in Taman Pura Kencana, Johor - Md Tahir, Ummu Salamah; Zainun, Noor Yasmin; Ahmad, Hilton; Khahro, Shabir Hussain; Alias, Ahmad Rizal (International Journal of Sustainable Construction Engineering and Technology, 2022)
Food waste is one of the critical issues which has been discussed in many countries including Malaysia. Apart from that, about 50% of food waste usually being dumped at landfill sites and incinerators which root to more problems towards the environment, economic and society. In this research, Taman Pura Kencana, Johor was chosen to identify the average total of food waste generation from selected households in 3 months from April 2021 to June 2021 and to determine decomposing days of food waste using BSFL. Raosoft Sample Size Calculator was used to calculate sample respondents bringing 48 households in this research. Hence, the average total of food waste generation from households per month was 1056.82 kg The collection of food waste from selected households in Taman Pura Kencana during the normal month of June was the highest compared to the fasting month in April and Eid month in May. 25 samples of food waste were examined to identify duration of decomposing days using BSFL based on pH, temperature and moisture content. The results showed that, the food waste successfully decompose after 10 days compare to control sample which was taking the longest time to fully decompose at about 90 days. The range of average temperature of the food waste using BSFL were 27? to 34?. The initial range of average pH value for the food waste samples were 3.22 to 4.00 while on the last decomposing days of the food waste samples were 7.06 to 7.12. Moisture content for food waste samples is 51% except for control sample. Inconclusion, BSFL were the ideal insects to decrease amount of food waste in landfills and incinerators as they could accelerate the time of composting food waste and could reduce the negative impacts towards the environment, economic and society.This research’s findings will help create awareness and a better understanding of how much food waste could be generated from residential area, as this contributes to many negative issues when discarding them through landfills and incinerators.